2019
DOI: 10.1093/treephys/tpz057
|View full text |Cite
|
Sign up to set email alerts
|

Sexually differential gene expressions in poplar roots in response to nitrogen deficiency

Abstract: Nitrogen (N) is a key nutrient impacting plant growth and physiological processes. However, the supply of N is often not sufficient to meet the requirements of trees in many terrestrial ecosystems. Because of differences in production costs, male and female plants have evolved different stress resistance strategies for N limitation. However, little is known about differential gene expression according to sex in poplars responding to N limitation. To explore sex-related constitutive defenses, Populus cathayana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…The differentially expressed targets, with respect to their cognate miRNAs, could be clustered into NBS-LRR, ubiquitination, pectate lyase, and so on. NBS-LRR genes were documented to enhance tolerance to abiotic stress (Li et al, 2017) and dramatically change under nitrogen deficiency in poplar (Song et al, 2019). In this study, the predicted novel miR0145-NBS-LRR interaction was identified, and its functions in response to Pi deficiency require further analysis.…”
Section: Masson Pinementioning
confidence: 88%
“…The differentially expressed targets, with respect to their cognate miRNAs, could be clustered into NBS-LRR, ubiquitination, pectate lyase, and so on. NBS-LRR genes were documented to enhance tolerance to abiotic stress (Li et al, 2017) and dramatically change under nitrogen deficiency in poplar (Song et al, 2019). In this study, the predicted novel miR0145-NBS-LRR interaction was identified, and its functions in response to Pi deficiency require further analysis.…”
Section: Masson Pinementioning
confidence: 88%
“…Recent studies on NUE mainly focused on the root system, and different zones of poplar roots showed distinct capacities for N absorption and assimilation because of differentially expressed microRNA (miRNA)-target pairs [ 15 ]. The results of transcriptome and metabolome analysis of poplar roots in response to N deficiency showed that males had a better osmotic adjustment ability and higher NUE, indicating a better stress tolerance ability compared with that of females [ 16 , 17 ]. We believe that there is a close relationship between roots and leaves in the form of a ‘source-sink’.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of transcriptomic data for male and female reproductive organs of P. balsamifera revealed gene expression trajectories during flower development and male-biased expression of two MADS-box genes, APETALA3 and PISTILLATA ( Cronk et al, 2020 ). Besides, in several studies of Populus species, sex-associated differences in gene expression were observed under particular, predominantly unfavorable, conditions ( Melnikova et al, 2017 ; Han et al, 2018 ; Song et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%